PROGRAM PENGEMBANGAN EKONOMI BERBASIS PONDOK PESANTREN - Firdha Aigha Suwito; Azhari Akmal Tarigan (Sekolah Tinggi Pariwisata Mataram, 2022)
This research aims to understand the Islamic boarding school-based economic development programs issued by the Regional Office of the Ministry of Religious Affairs of North Sumatera Province. The resources owned by Islamic boarding schools can be developed as facilities in the practice of Islamic Economics activities. The method used in this research is a qualitative method with a descriptive approach. The data used is primary data, namely the results of direct observations in internship activities for one month in the Islamic Religious Education Field Office of the Ministry of Religious Affairs of North Sumatera Province, and secondary data used are scientific journal articles, documents, and other related and relevant sources. As for the results obtained from this research, the economic development program based on boarding school in the Regional Office of the Ministry of Religious Affair of North Sumatera Province is basically the same as the program of the Ministry of Religion of the Republic of Indonesia, namely by issuing a mapping and profiling program for 100 Economic Islamic Boarding Schools. Specifically, the programs issued include: the Pesantrenpreneur program, the Santripreneur Movement, 100 BUM-Pes (Islamic Boarding Schools Owned Enterprises), launching the Islamic Boarding School Community Economic Hub activities, Communities of Practice, as well as replicating or developing up to 1,500 Islamic boarding schools. The aim of this program will be able to bring out Islamic boarding schools that are independent in various aspects. The development of the Islamic boarding school-based economy is expected to advance the economic level of the Islamic boarding school itself and the surrounding community, and also can advance and make the Islamic boarding school as the center for Islamic Economics practice.